2022
DOI: 10.1128/jvi.00508-22
|View full text |Cite
|
Sign up to set email alerts
|

DLK-Dependent Biphasic Reactivation of Herpes Simplex Virus Latency Established in the Absence of Antivirals

Abstract: Herpes simplex virus-1 (HSV-1) enters a latent infection in neurons and periodically reactivates. Reactivation manifests as a variety of clinical symptoms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 124 publications
1
14
0
Order By: Relevance
“…In latently infected neurons, we observed enrichment of H3K27me3 on approximately 31% of latent HSV-1 genomes based on a NucSpotA intensity ratio above 1.5. This is consistent with previous observations that H3K27me3 is both enriched on the latent HSV genomes and its removal is important in reactivation (12,15,34,35,(78)(79)(80)(81). These data also highlight the potential heterogeneity in the epigenetic nature of latent HSV genomes, which may relate to different levels of expression of the latency-associated transcript between individual neurons or differences in sub-nuclear genome localization (82,83).…”
Section: Analysis Of Individual Hsv-1 Genome Foci For Co-localization...supporting
confidence: 92%
“…In latently infected neurons, we observed enrichment of H3K27me3 on approximately 31% of latent HSV-1 genomes based on a NucSpotA intensity ratio above 1.5. This is consistent with previous observations that H3K27me3 is both enriched on the latent HSV genomes and its removal is important in reactivation (12,15,34,35,(78)(79)(80)(81). These data also highlight the potential heterogeneity in the epigenetic nature of latent HSV genomes, which may relate to different levels of expression of the latency-associated transcript between individual neurons or differences in sub-nuclear genome localization (82,83).…”
Section: Analysis Of Individual Hsv-1 Genome Foci For Co-localization...supporting
confidence: 92%
“…This suggests a model in which transcriptional silencing is either established quickly yielding a low copy number latency-like infection or silencing takes place more slowly and permits some replication but is ultimately abortive and again resolves as a latent infection. This is supported by recent studies using a new reporter virus (HSV-1 Stayput-GFP) that is fully competent for DNA replication and gene expression but cannot spread from neuron-to-neuron [66]. With this virus, latent infections of murine primary SCG and TG neurons can be readily established and maintained for extended periods in the absence of antiviral treatments.…”
Section: Neuronal Latency Modelsmentioning
confidence: 89%
“…Precision studies are needed to determine if there are additional changes in chromatin composition or post-translational modification over time that can explain why reactivation is less efficient after sustained periods. Studies using the new spread-deficient reporter found that although genome copy number and LAT levels remained relatively constant, the proportion of neurons undergoing reactivation at 30 days post-infection was much reduced compared to 8 or 16 days [66].…”
Section: Looking To the Horizonmentioning
confidence: 95%
“…By expressing HSV-1 ICP0 during this initial phase, the action of IFN is temporally restricted, thereby enabling subsequent lytic replication [43]. Superinfection was used to induce rapid and robust reactivation of HSV, which is likely to result in the delivery of viral tegument proteins [44]. It is therefore possible that UV-inactivated herpesvirus may provide a substantial supply of viral proteins, thereby shortening the duration of the first phase and increasing the success of reactivation.…”
Section: Discussionmentioning
confidence: 99%